Electrocardiographic safety evaluation of dihydroartemisinin piperaquine in the treatment of uncomplicated falciparum malaria. - Mytton, O; Ashley, E; Peto, L; Price, R; La, Y; Hae, R; Singhasivanon, P; White, N; Nosten, F (2007)
Dihydroartemisinin-piperaquine (DP) could become a leading fixed combination malaria treatment worldwide. Although there is accumulating evidence of efficacy and safety from clinical trials, data on cardiotoxicity are limited. In two randomized controlled trials in Thailand, 56 patients had ECGs performed before treatment, 4 hours after the first dose, and 4 hours after the last dose. The mean (95% CI) changes in QTc interval (Bazett's correction) were 2 (-6 to 9) ms and 14 (7 to 21) ms, respectively. These small changes on the third day of treatment are similar to those observed elsewhere in the convalescent phase following antimalarial treatment with drugs known to have no cardiac effects and are therefore likely to result from recovery from acute malaria and not the treatment given. At therapeutic doses, DP does not have clinically significant effects on the electrocardiogram.